2022
DOI: 10.3389/fnut.2021.767535
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids Improve Functionality of High-Density Lipoprotein in Individuals With High Cardiovascular Risk: A Randomized, Parallel, Controlled and Double-Blind Clinical Trial

Abstract: Omega-3 (ω-3) fatty acids have been extensively studied for primary and secondary prevention of cardiovascular health, but their ability to modulate HDL functionality remains unclear. The purpose of this study was to investigate the role of ω-3, rich in eicosapentaenoic (EPA) and docosahexaenoic (DHA), on HDL functionality. For that, 147 individuals with high cardiovascular risk were randomized in ω-3 (1 g of fish oil each - 370 mg of EPA and 230 mg of DHA, 3 times per day total EPA+DHA = 1,800 mg) or ω-6 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Our results showed a significant increase in EPA and DHA as components of lipids carried by HDLs. Such increments were similar to that observed in the plasma of patients with high cardiovascular risk treated with 1800 mg/d of n-3 as fish oil, and who reached 220.3% and 68.3% of EPA and DHA increase in plasma, respectively [ 15 ]; this study also demonstrated a modification of HDL subclasses induced by n-3 supplementation. Conversely, we did not observe any change in HDL size distribution or in lipids of HDL subclasses, probably because our study group was more homogeneous in terms of risk factors than the previous report [ 15 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results showed a significant increase in EPA and DHA as components of lipids carried by HDLs. Such increments were similar to that observed in the plasma of patients with high cardiovascular risk treated with 1800 mg/d of n-3 as fish oil, and who reached 220.3% and 68.3% of EPA and DHA increase in plasma, respectively [ 15 ]; this study also demonstrated a modification of HDL subclasses induced by n-3 supplementation. Conversely, we did not observe any change in HDL size distribution or in lipids of HDL subclasses, probably because our study group was more homogeneous in terms of risk factors than the previous report [ 15 ].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, DHA may contribute to the increase the anti-inflammatory properties of HDLs since this fatty acid, as well as EPA, are precursors of resolvins (inflammation-resolving mediators) via the lipoxygenase pathway [ 24 ]. Finally, it cannot be discarded that the reduction in some other n-6 fatty acids in HDL may also contribute to the beneficial effects of n-3 supplementation [ 15 ]. This issue needs to be addressed in further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be responsible for the worse morbidity of their COVID‐19 course owing to lack of these resolution factors (Pal et al 2020 ). EPA- and DHA-linked HDL improves it antioxidant and enzyme functions (Cartolano et al 2022 ).…”
Section: Resolving Mediators In Covid-19mentioning
confidence: 99%
“…In addition to the emerging measures of healthspan, reports also suggest that fish oils exert beneficial health effects via the modulation of lipid profiles, primarily through triglycerides (Tg), but also through modification of high-and low-density lipoproteins (HDL and LDL, respectively), though results for the latter are less consistent [17][18][19][20][21][22][23].…”
mentioning
confidence: 99%